Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jafc.1c00825
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Fungicide Famoxadone: Stereoselective Bioactivity, Aquatic Toxicity, and Environmental Behavior in Soils

Abstract: In this study, the stereoselective bioactivity, acute toxicity, and environmental fate for famoxadone enantiomers were reported for the first time. Five representative pathogens (e.g., Alternaria solani) were used to investigate enantioselective activity, and three non-target organisms (e.g., Selenastrum bibraianum) were used to evaluate acute toxicity. S-Famoxadone was 3.00–6.59 times more effective than R-famoxadone. R-Famoxadone also showed 1.80–6.40 times more toxicity than S-famoxadone toward S. bibraianu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[29][30][31][32] Furthermore, the phenyl and diphenyl ether fragments were also frequently observed in many fungicides, such as metrominostrobin, famoxadone, fentursm and oxycarboxin. [33][34][35][36] These findings indicated that the above-mentioned molieties were all important substructures for the discovery of new fungicides.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[29][30][31][32] Furthermore, the phenyl and diphenyl ether fragments were also frequently observed in many fungicides, such as metrominostrobin, famoxadone, fentursm and oxycarboxin. [33][34][35][36] These findings indicated that the above-mentioned molieties were all important substructures for the discovery of new fungicides.…”
Section: Introductionmentioning
confidence: 81%
“… [26–28] On the other hand, the hydrazide group was proved to be a key pharmacophore in some fungicides and insecticides such as benquinox, fennamidone, RH‐5849 and tebufenozide [29–32] . Furthermore, the phenyl and diphenyl ether fragments were also frequently observed in many fungicides, such as metrominostrobin, famoxadone, fentursm and oxycarboxin [33–36] . These findings indicated that the above‐mentioned molieties were all important substructures for the discovery of new fungicides.…”
Section: Introductionmentioning
confidence: 97%
“…Chirality is an essential attribute of nature and an important symbol of the difference between living matter and nonliving matter. The physiology of many chemical substances carries out the chemical processes in the phenomena of life in a highly asymmetric environment. , The generation of function is often attributed to the recognition and matching of chiral molecules. , With the development of research, people’s understanding of life processes is deepening, and the study of chirality has aroused wide interest in the scientific community. In recent years, chiral pesticides, which contain only one or two highly effective isomers, have been widely used in pest control in agricultural planting because of their advantages of high efficiency, low toxicity, strong selectivity, and low residual amount. As a key pesticide for disease prevention and control in agriculture, agricultural fungicides have also been widely studied in recent years. Among the current commercial agricultural fungicides, nearly 32% are chiral, and most of the biological activity and toxicity of chiral fungicides are closely related to their configuration. Therefore, effectively enriching chiral fungicides with biological activity and maximizing the utilization rate of chiral pesticides through controlled release is still a serious challenge …”
Section: Introductionmentioning
confidence: 99%
“…Commercial FEN is a racemate, which contains two enantiomers, R -FEN and S -FEN. The enantiomers often exhibit significant differences in biological processes, including toxicity, bioactivity, bioaccumulation, degradation, and metabolism. The study has indicated that FEN is moderately persistent in acidic and alkaline soils with a degradation half-life ( t 1/2 ) ranging from 13.7 to 31.1 days . Moreover, the degradation of FEN enantiomers is slightly enantioselective, where S -FEN degrades faster than R -FEN in alkaline soil .…”
Section: Introductionmentioning
confidence: 99%